Eleanor vs. Ike - Gerber, Robin (New York, NY : Avon A, 2008)
In this what-if novel, during the 1952 Democratic convention, Adlai Stevenson suffers a heart attack and dies on stage moments before he accepts the nomination. The popular Eleanor Roosevelt, a widow since 1945, is quickly brought in to take his place and run against Eisenhower. Her campaign rallies the support of women, unions and African-Americans, but even her own party doubts that Americans will elect a woman president, and as the campaign progresses, the Ku Klux Klan threatens to assassinate her and powerful enemies try to destroy her good name.
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Fiction; Eisenhower, Dwight D. -- 1890-1969 -- Fiction; Presidents -- United States -- Election -- 1952 -- Fiction; Political fiction; Alternative histories (Fiction)